Chalk proceedings of the International Chalk Symposium held at Brighton Polytechnic on 4-7 September 1989. (Thomas Telford, 1990)
Papers cover: the engineering stratigraphy and palaeogeography for the chalk of the Anglo-Paris basin; a survey of macro and micro-fracturing in Yorkshire chalk; studies in the influence of water in calcite; logging of chalk for engineering purposes; and much more.
Keywords: Chalk -- Congresses.; elektronické knihy; electronic books